Is the functional movement screen a feasible and effective tool for pre-season screening in junior elite Australian footballers? - Debenedictis, T. A.; Fuller, J. T.; Magarey, M.; Townsley, S.; Lynagh, M.; Gleeson, C.; Zacharia, A.; Thomson, S.; Chalmers, S. (Journal of Australian Strength and Conditioning, 2016)
Australian football (AF) is a contact sport that features a high injury rate at both junior and senior levels. The ability to identify athletes that are at a high risk of injury based on musculoskeletal movement patterns is of great benefit. Junior clubs often require simple and time-efficient procedures due to the large squad numbers and lack of full-time staff. The Functional Movement Screen (FMS) provides a potential method for the movement screening of large numbers of athletes allowing those athletes with potentially the greatest risk of injury to be identified. The purpose of this study was to explore the feasibility and efficacy of the FMS as a means of assessing the injury risk of a large number of elite junior AF athletes.